Intelligensietoetse - Kriel, A. P; Neser, G. O; Schoonees, L. J.(Lukas Jakobus),1899-; Wolfaard, C. J (Stellenbosch : Stellenbosch University, 2012)
Tesis (B. Ed.) -- Universiteit van Stellenbosch, 1925.